Characteristics and potential climatic significance of "miniature ice caps" (crest- and cornice-type low-altitude ice archives). Issue 168 (8th September 2004) - Haeberli, Wilfried; Frauenfelder, Regula; Kääb, Andreas; Wagner, Stephan
Abstract: Long-term ice-core records of Alpine glaciers are usually taken from cold-firn areas at high altitudes, as on Mont Blanc and Monte Rosa. Perennial ice bodies at lower altitudes, however, also bear information about the past. Recent findings from the remains of such ice (the Oetztal iceman found in Austria; wooden bows at Lötschen Pass, Switzerland) clearly indicate the hitherto little-recognized fact that small, more-or-less static perennial ice bodies which are cold and frozen to the underlying bedrock may contain very old ice and, hence, important palaeoclimatic information about warm periods with minimum ice extent in the Alps. Since autumn 1998, investigations have been initiated on a crest-type location or "miniature ice cap" at Piz Murtèl, Engadine, Swiss Alps. First results from shallow drilling, temperature data-logging, geodetic surveying, visual observation, finite-element modelling of simplified basic two-dimensional configurations and comparison to earlier measurements at similar sites provide promising perspectives concerning a little-studied phenomenon with considerable scientific-environmental research potential. Specific characteristics of the investigated site, and probably of many other comparable mountain sites, are: cold ice (about –4°C at 10 m depth), no basal sliding, small mass turnover, striking lack of a firn zone, accumulation mainly by superimposed ice, and direct access to old layers (centuries, millennia?) at the ice/bedrock interface.